An Ex Ante Approach to the Resilience and Recovery Plan’s Impacts on Sustainable Tourism in Algarve and Alentejo - Bernardo Valente; Erika Džajić Uršič (Tourism and Hospitality)
The European Union has been trying to adjust its tourism policy in response to the challenges posed by the recent COVID-19 pandemic. The funding of the EU Cohesion Policy has been one of the primary mechanisms guaranteeing that all regions can be prepared to receive tourists and cope with the sustainability challenges the pandemic has raised. The recovery and resilience plan (PRR) is the most recent instrument created to help economic growth in most European Union countries. The implementation of the PRR in Algarve and Alentejo has been fundamental to understanding the Portuguese tourism sector, as these regions are heavily dependent on tourism sector revenue and were hit hard by the consecutive lockdowns in recent years. Therefore, this policy, in brief, critically assesses the tourism-related projects that received funding from the PRR until November 2023 (ex ante) and their potential to guarantee long-term tourism sustainability in Algarve and Alentejo. Despite not achieving the expected efficiency results due to delays in project execution and low investment, the PRR is still a positive upgrade for tourism-related policy in Algarve and Alentejo.